Intraoral spindle-cell lipoma with chondroid differentiation: importance in the diagnosis of oral lesions presenting chondroid tissue - Ademar Takahama Junior; Michele F. Brantes; Jorge E. Leon; Adriele F. Gouvêa; Oslei P. Almeida
ABSTRACT Lipomas are benign neoplasms of adipose tissue presenting several histologic variants, which can be rarely found in the oral cavity. We present a case of a 62-year-old woman with a submucous nodule located in the tongue. Histopathological examination revealed an encapsulated tumor composed of myxoid tissue, spindle cells and mature adipocytes in transition to cartilaginous tissue. The final diagnosis was spindle-cell lipoma with myxoid change and chondroid differentiation. No sign of recurrence was found after five years. The diagnosis of intraoral mesenchymal lesions with chondroid differentiation requires careful histologic examination, mainly to differentiate between benign and malignant lesions.